2011
DOI: 10.1002/art.30364
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritic synovial tissue inhibition of proteoglycan production in human osteoarthritic knee cartilage: Establishment and characterization of a long-term cartilage-synovium coculture

Abstract: Objective. Although both cartilage and synovium are affected in osteoarthritis (OA), no in vitro coculture models of human OA tissue have been described. The aim of this study was to develop an in vitro model that includes both the synovium and cartilage of patients with knee OA.Methods. Explants of human OA cartilage and synovium were cultured alone or in coculture for 21 days. Histologic evaluation and analyses of lactate dehydrogenase release, matrix metalloproteinase (MMP) activity, content, release, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 99 publications
7
75
1
2
Order By: Relevance
“…These studies have demonstrated the enhanced production of key inflammatory mediators from chondrocytes exposed to OA synovial fluid or the synovium itself, which may act to further stimulate macrophage inflammation. 12,56,57,68,69 Cumulatively, our results agree well with changes seen in early OA and with similar in vitro model systems using NCs.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These studies have demonstrated the enhanced production of key inflammatory mediators from chondrocytes exposed to OA synovial fluid or the synovium itself, which may act to further stimulate macrophage inflammation. 12,56,57,68,69 Cumulatively, our results agree well with changes seen in early OA and with similar in vitro model systems using NCs.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, the cytokine expression data are also similar to two previous reportsone in which healthy human chondrocytes were treated with the synovial fluid of OA patients, 68 and another wherein healthy cartilage explants were cocultured with synovium from OA patients. 69 Effect of coculture on AMs. In addition to NC response, we also investigated the phenotypic shift of AMs cocultured with NCs, which has generally remained unexplored in the literature.…”
Section: D System To Study Effects Of Osteoarthritic Inflammationmentioning
confidence: 99%
“…36,37 Long-term coculture models of synovial tissue and cartilage explants highlight the role of activated synoviocytes in cartilage destruction associated with OA. 38 The synovial tissue was found to secrete high levels of interleukin (IL)-6, IL-8, and osteoprotegerin, and to produce cytokines throughout the culture period. Furthermore, cartilage explant glycosaminoglycan (GAG) content was found to be significantly lower following a 21-day exposure to the synovial tissue compared with cartilage monocultures.…”
Section: Synovitismentioning
confidence: 99%
“…Furthermore, cartilage explant glycosaminoglycan (GAG) content was found to be significantly lower following a 21-day exposure to the synovial tissue compared with cartilage monocultures. 38 It is evident that pro-inflammatory mediators produced by inflamed synovium are capable of driving the progression of OA through induction of destructive processes in cartilage (Table 1), and the abundance of such catabolic factors in an osteoarthritic joint may greatly impede cartilage tissue engineering strategies.…”
Section: Synovitismentioning
confidence: 99%
See 1 more Smart Citation